Photodynamic Antimicrobial Chemotherapy: Advancements in Porphyrin-Based Photosensitize Development - Oyim, James; Omolo, Calvin A.; Amuhaya, Edith K. (Frontiers in Chemistry, 2021)
The shrinking of available drugs against microbes is worsening with the current global crisis of antimicrobial resistance. This calls for innovative strategies of combating antimicrobial resistance. Photodynamic Antimicrobial Chemotherapy (PACT) is a relatively new method that utilizes the combined action of light, oxygen, and a photosensitizer to bring about destruction of microorganisms. This technique has been found to be effective against a wide spectrum of microorganisms, including bacteria, viruses, and fungi. Of greater interest is their ability to destroy resistant strains of microorganisms, and in effect help in combating the emergence of antimicrobial resistance. This manuscript reviews porphyrins and porphyrin-type photosensitizers that have been studied in the recent past with a focus on their structure-activity relationship.